Assessment of agro-morphological traits, grain physical and physico-chemical properties in the Indian aromatic rice (Oryza sativa) germplasm - DIXIT, DEEPSHIKHA; SIDDIQUI, N; BOLLINEDI, HARITHA; KRISHNAN, GOPAL; MALIK, ANKIT; BHOWMICK, P K; ELLUR, R K; NAGARAJAN, M; VINOD, K K; SINGH, A K (The Indian Journal of Agricultural Sciences, 2022)
Information on genetic diversity with respect to various agro-morphological traits and eating and cooking quality traits plays a key role in the improvement of rice (Oryza sativa L.). With this aim, we have characterized a set of 98 indigenous aromatic rice germplasm accessions for four agro-morphological, two physical and two physico-chemical traits. Significant variation was observed among the cultivars for all the traits. Correlation analysis showed negative correlation of DFF with KLBC (r= -0.29; p=0.022) and kernel L/W ratio (r= -0.25; p=0.003), while PL was significantly and positively correlated with KLBC (r=0.38; p=0.000) and kernel L/W ratio (r=0.43; p=0.0649). KLBC showed highly significant positive correlation with GC (r=0.22; p=0.614) while between AAC and GC a significant negative correlation was observed (r= -0.38; p=0.000).